Bevacizumab loaded CalliSpheres® bronchial arterial chemoembolization combined with immunotherapy and targeted therapy for advanced lung adenocarcinoma - Liu, Haitao; Li, Yahua; Li, Zongming; Han, Xinwei; Ren, Kewei (Frontiers in Pharmacology, 2023)
Background: As a new drug delivery and embolization system, drug-eluted bronchial artery chemoembolization (DEB-BACE) can not only embolize the tumor blood supply artery but also load chemotherapy drugs and slowly release them into the local environment. Bevacizumab (BEV) combined with chemotherapy drugs has attained significant achievements in the first-line treatment of advanced non-squamous non-small cell lung cancer (NSCLC). The role of BEV-loaded DEB-BACE combined with immunotherapy and targeted therapy in patients with lung adenocarcinoma (LUAD) is unclear. This study was designed to evaluate the efficacy and safety of bevacizumab-loaded CalliSpheres® bronchial arterial chemoembolization combined with immunotherapy and targeted therapy in patients with lung adenocarcinoma. Methods: Nine patients with LUAD who received BEV-loaded CalliSpheres® BACE combined with immunotherapy and targeted therapy from 1 Jan 2021 to Dec 2021 were included in this study. The primary endpoint was the disease control rate (DCR) and the objective response rate (ORR). The secondary endpoints were the overall survival rates (OS) at 6 months and 12 months. The tumor response was evaluated according to the mRECIST standard. Safety was assessed by the occurrences of adverse events and the severity of the adverse events. Results: All patients received CalliSpheres® BACE loaded with BEV (200 mg) in combination with immunotherapy and targeted therapy. A total of nine patients received the BACE procedures 20 times, four of them received a third session of BACE, three underwent a second session of DEB-BACE, and two underwent one cycle of DEB-BACE. Partial response and stable disease were found in seven (77.8%), and two (22.2%) patients, respectively, 1 month after the last multimodal treatment. The ORR at 1, 3, 6, and 12 months was 77.8%, 66.7%, 44.4%, and 33.3%, respectively, while the DCR was 100%, 77.8%, 44.4%, and 33.3%, respectively. The OS rates at 6-and 12-month were 77.8% and 66.7%, respectively. There were no serious adverse events. Conclusion: BEV-loaded CalliSpheres® transcatheter bronchial arterial chemoembolization combined with immunotherapy and targeted therapy is a promising and well-tolerated treatment for patients with lung adenocarcinoma.